Heat and Dehydration Additively Enhance Cardiovascular Outcomes following Orthostatically-Stressful Calisthenics Exercise - Akerman, Ashley P.; Lucas, Samuel J. E.; Katare, Rajesh; Cotter, James D. (Frontiers in Physiology, 2017)
Exercise and exogenous heat each stimulate multiple adaptations, but their roles are not well delineated, and that of the related stressor, dehydration, is largely unknown. While severe and prolonged hypohydration potentially “silences” the long-term heat acclimated phenotype, mild and transient dehydration may enhance cardiovascular and fluid-regulatory adaptations. We tested the hypothesis that exogenous heat stress and dehydration additively potentiate acute (24 h) cardiovascular and haematological outcomes following exercise. In a randomised crossover study, ten physically-active volunteers (mean ± SD: 173 ± 11 cm; 72.1 ± 11.5 kg; 24 ± 3 y; 6 females) completed three trials of 90-min orthostatically-stressful callisthenics, in: i) temperate conditions (22˚C, 50% rh, no airflow; CON); ii) heat (40˚C, 60% rh) whilst euhydrated (HEAT), and iii) heat with dehydration (no fluid ~16 h before and during exercise; HEAT+DEHY). Using linear mixed effects model analyses, core temperature (TCORE) rose 0.7˚C more in HEAT than CON (95% CL: [0.5, 0.9]; p < 0.001), and another 0.4˚C in HEAT+DEHY ([0.2, 0.5]; p < 0.001, vs. HEAT). Skin temperature also rose 1.2˚C more in HEAT than CON ([0.6, 1.8]; p < 0.001), and similarly to HEAT+DEHY (p = 0.922 vs. HEAT). Peak heart rate was 40 bmin-1 higher in HEAT than in CON ([28, 51]; p < 0.001), and another 15 bmin-1 higher in HEAT+DEHY ([3, 27]; p = 0.011, vs. HEAT). Mean arterial pressure at 24-h recovery was not consistently below baseline after CON or HEAT (p ≥ 0.452), but was reduced 4 ± 1 mm Hg after HEAT+DEHY ([0, 8]; p = 0.020 vs. baseline). Plasma volume at 24 h after exercise increased in all trials; the 7% increase in HEAT was not reliably more than in CON (5%; p = 0.335), but was an additional 4% larger after HEAT+DEHY ([1, 8]; p = 0.005 vs. HEAT). Pooled-trial correlational analysis showed the rise in TCORE predicted the hypotension (r = -0.4) and plasma volume expansion (r = 0.6) at 24 h, with more hypotension reflecting more plasma expansion (r = -0.5). In conclusion, transient dehydration with heat potentiates short-term (24-h) haematological (hypervolaemic) and cardiovascular (hypotensive) outcomes following callisthenics.